Speeches...during the period September 2004 to May 2005 - Bourne, Compton (CDB WildeyBB, 2005)
Looks at higher education, the role of the CDB, irrigation in Jamaica and poverty and its alleviation. Focuses on the Regional Development Fund and examines the competitiveness challenge in Barbados.